Searches for violation of lepton flavour and baryon number in tau lepton decays at LHCb - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; Grünberg, Oliver; et al. (Physics letters, 2013)
Searches for the lepton flavour violating decay τ−→μ−μ+μ− and the lepton flavour and baryon number violating decays τ−→p¯μ+μ− and τ−→pμ−μ− have been carried out using proton-proton collision data, corresponding to an integrated luminosity of 1.0 fb−1, taken by the LHCb experiment at s=7 TeV. No evidence has been found for any signal, and limits have been set at 90% confidence level on the branching fractions: B(τ−→μ−μ+μ−)<8.0×10−8, B(τ−→p¯μ+μ−)<3.3×10−7 and B(τ−→pμ−μ−)<4.4×10−7. The results for the τ−→p¯μ+μ− and τ−→pμ−μ− decay modes represent the first direct experimental limits on these channels.